The communities of the nematodes, bacteria, and fungi and the soil's organic matter in an agroforestry ecosystem in Croatia - Puškarić, Josipa; Jović, Jurica; Ivezić, Vladimir; Popović, Brigita; Paponja, Ivan; Brmež, Mirjana (2021)
An above ground plant diversity affects a below-ground biodiversity. A soil fauna diversity is important for the ecosystems" sustainability. It reflects both the abiotic conditions and the soil"s biotic activity. This study"s objective was to assess the effect of an agroforestry system on the nematode abundance and trophic group distribution and on the bacterial and fungal abundance in the soil, as well as to analyze the links between a nematode abundance, trophic group patterns, soil"s microbiological status and the organic matter. A field experiment was conducted during two years in three treatments and three sampling periods. The treatments were as follows: an agricultural crop (C), a permanent walnut plantation (W), and a permanent walnut plantation with an agricultural crop (C + W). The nematodes were extracted, counted, processed and mounted on slides and ultimately determined and assigned to the trophic groups. The bacteria and fungi were extracted from the soil, grown on the plates, and counted. Our findings suggest that the studied agroforestry system (C+W) has exerted a positive effect on the soil nematodes, bacteria, and fungi, manifested as the statistically highest abundance of bacteria and fungi, but also as the highest abundance of nematodes and of a diversity of the nematode genera. The highest content of the organic matter was detected in the treatment C + W in the first sampling and in the treatments C + W and W in the second sampling. We have concluded that the combination of an agricultural crop and a permanent plantation has a great potential for better ecosystem stability and sustainability regardless of some deviations in our results. We believe that further research is necessary because the different agroforestry ecosystems may have different impacts on the soil fauna.
Biljna raznolikost iznad tla utječe na biološku raznolikost u tlu. Raznolikost faune tla važna je za održivost ekosustava, a odražava i abiotske uvjete i biotičku aktivnost tla. Cilj ovoga istraživanja bio je utvrditi utjecaj agrošumarskih sustava na faunu nematoda u tlu, brojnost nematoda, distribuciju trofičkih grupa nematoda i brojnost bakterija i gljiva u tlu te analizirati povezanost između hranidbenih grupa nematoda, mikrobiološkoga statusa tla i humusa. Poljski pokus proveden je tijekom dviju godina u trima tretmanima i tijekom triju vremena uzorkovanja. Tretmani su bili sljedeći: poljoprivredna kultura (C), trajni nasad oraha (W) i trajni nasad oraha s poljoprivrednom kulturom (C + W). Nematode su izdvojene, prebrojene, pripremljene u preparate, determinirane te podijeljene u trofičke grupe. Bakterije i gljive su izdvojene iz tla, uzgajane na podlogama i prebrojene. Naši rezultati sugeriraju da je proučeni agrošumarski sustav (C + W) imao pozitivan utjecaj na nematode, bakterije i gljive u tlu, što je prikazano kao statistički najveća brojnost bakterija i gljiva, ali i kao najveća brojnost nematoda i bioraznolikost rodova nematoda. Najveći sadržaj humusa pronađen u prvome uzorkovanju jest onaj u tretmanu C + W, a u drugome uzorkovanju u tretmanima C + W i W. Zaključili smo da kombinacija poljoprivredne kulture i trajnih nasada ima velik potencijal za bolju stabilnost i održivost ekosustava, bez obzira na neka odstupanja u našim rezultatima. Smatramo da su potrebna daljnja istraživanja, jer različiti agrošumarski ekosustavi mogu imati različit utjecaj na faunu tla.
Bibliografija: 42 jed.
Summary ; Sažetak.
Keywords: Fauna tla -- Mikroorganizmi -- Nematode -- Orasi -- Nasadi -- Poljoprivredna kultura